2011
DOI: 10.1177/0020715211412115
|View full text |Cite
|
Sign up to set email alerts
|

Blocked mobility or unemployment risk? Labour market transitions of natives and immigrants in Switzerland

Abstract: Cross-sectional literature has shown that in Switzerland as elsewhere immigrants are more penalized than the native-born population both considering the unemployment risk and their position in the employment structure. Using a longitudinal framework, the present article focuses on a comparison between male immigrants and natives in the Swiss labour market, analysing two risks: the risk of unemployment and the risk of entrapment in unskilled occupations. In the first part of the article, using a dynamic random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…Analysis corroborates that Italians and Spaniards were among those foreign groups with a stronger disadvantageous occupational position in 1980 (Golder, 2001;Lagan a, 2013), supporting findings on the limited influence of human capital in reversing this situation. This finding is in line with the human capital hypothesis, which explains the privileged labour positions of those collectives of foreign workers who are better qualified on average than the local labour force.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Analysis corroborates that Italians and Spaniards were among those foreign groups with a stronger disadvantageous occupational position in 1980 (Golder, 2001;Lagan a, 2013), supporting findings on the limited influence of human capital in reversing this situation. This finding is in line with the human capital hypothesis, which explains the privileged labour positions of those collectives of foreign workers who are better qualified on average than the local labour force.…”
Section: Discussionsupporting
confidence: 60%
“…Effectively, even if the low educational levels of cohorts of foreign workers from Italy and Spain, as well as from Portugal, the former Yugoslavia, and Turkey, explained their less favourable occupational outcomes, they were also less able to translate their credentials into a good job than natives and other groups. Analysis corroborates that Italians and Spaniards were among those foreign groups with a stronger disadvantageous occupational position in 1980 (Golder, 2001;Lagan a, 2013), supporting findings on the limited influence of human capital in reversing this situation. Thus, the negative skill-selectivity of "early" migrants from Italy and Spain is not the only explanation for the overrepresentation of these collectives in working-class occupations FIGURE 2 ACCESS TO SALARIAT AND INTERMEDIATE OCCUPATIONS IN 1980AND 2010 during the guest worker period.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…1 Today, the children of immigrants represent a large group of inhabitants in the urban areas of Western Europe and the United States: "the large size of the second generation guarantees that these individuals will have a profound impact on the cultural and ethnic differences within their societies" (Crul and Mollenkopf 2012:3). However, research on these populations shows that social and ethnic origins still strongly determine the life course of the second generation, particularly in terms of education and training; these origins also impact these populations' transition into the labor market (Portes et al 2005;Lagana 2011). Specifically, Reisel et al (2012) showed that the most marginalized minorities experience the greatest difficulties in Western European and US cities.…”
mentioning
confidence: 99%